Decoding the host–pathogen interspecies molecular crosstalk during oral candidiasis in humans: an in silico analysis - Kabir, Ali Rejwan; Chaudhary, Anis Ahmad; Aladwani, Malak O.; Podder, Soumita (Frontiers in Genetics, 2023)
Introduction The objective of this study is to investigate the interaction between Candida albicans and human proteins during oral candidiasis, with the aim of identifying pathways through which the pathogen subverts host cells. Methods A comprehensive list of interactions between human proteins and C. albicans was obtained from the Human Protein Interaction Database (HPIDB) using specific screening criteria. Then, the genes that exhibit differential expression during oral candidiasis in C. albicans were mapped with the list of human-candida interactions to identify the corresponding host proteins. The identified host proteins were further compared with proteins specific to the tongue, resulting in a final list of 99 host proteins implicated in oral candidiasis. The interactions between host proteins and C. albicans proteins were analysed using the STRING database, enabling the construction of PPINs. Similarly, the gene regulatory network of candida proteins was reconstructed using data from the Pathoyeastract and STRING databases. Core module proteins within the targeted host PPIN were identified using the Moduland, a Cytoscape plug-in. The expression levels of the core module proteins under diseased conditions were assessed using data from the GSE169278 dataset. To gain insights into the functional characteristics of both host and pathogen proteins, ontology analysis was conducted using Enrichr and YeastEnrichr, respectively. Result The analysis revealed that three candida proteins, HHT21, CYP5, and KAR2, interact with three core host proteins, namely ING4 (in the DNMT1 module), SGTA, and TOR1A. These interactions potentially impair the host's immediate immune response against the pathogen. Additionally, differential expression analysis of fungal proteins and their Transcription Factors (TFs) in candida-infected oral cell lines indicated that Rob1p, Tye7p, and Ume6p could be considered as candidate TFs involved in instigating pathogenesis of oral candidiasis during host infection. Conclusions Our study provides molecular map of host-pathogen interaction during oral candidiasis along with potential targets for designing regimens to overcome oral candidiasis, particularly in immunocompromised individuals.